2019
DOI: 10.1123/japa.2018-0232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on Cerebral Hemodynamics and Health-Related Outcomes in Older Community Adults at Risk of Ischemic Stroke: A Randomized Controlled Trial

Abstract: This study investigated the effects of Tai Chi compared with no exercise control on the cerebral hemodynamic parameters and other health-related factors in community older adults at risk of ischemic stroke. A total of 170 eligible participants were randomly allocated to Tai Chi or control group. The cerebral hemodynamic parameters and physical fitness risk factors of cardiovascular disease were measured at baseline, 12 weeks, and 24 weeks. After the 12-week intervention, Tai Chi significantly improved the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Studies have shown that the cerebral cortex is in a "relaxed" state when practising tai chi, which is a state of protective inhibition that can reduce the excitability of the sympathetic nervous system, leading to a decrease in norepinephrine and epinephrine, which, in turn, can reduce vasoconstrictive enzyme activity. During tai chi, the tissue is stimulated to release histamine, irritants and other substances, which relaxes the blood vessels and reduces BP (13). One study showed that tai chi promoted health, prevented disease, and had a positive effect on arterial stiffness and static/dynamic balance (15).…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the cerebral cortex is in a "relaxed" state when practising tai chi, which is a state of protective inhibition that can reduce the excitability of the sympathetic nervous system, leading to a decrease in norepinephrine and epinephrine, which, in turn, can reduce vasoconstrictive enzyme activity. During tai chi, the tissue is stimulated to release histamine, irritants and other substances, which relaxes the blood vessels and reduces BP (13). One study showed that tai chi promoted health, prevented disease, and had a positive effect on arterial stiffness and static/dynamic balance (15).…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…It is considered a pleasurable activity that combines meditation with gentle movements (10). A growing body of research has shown that tai chi strengthens the joints, modulates pressure receptors in the aortic arch and carotid sinus, and has a role in lowering BP and expanding the coronary arteries (11)(12)(13).…”
mentioning
confidence: 99%
“…Aerobic activities can mitigate or even reverse arterial stiffness by fostering arterial remodeling, reducing sympathetic nervous activity, and enhancing cerebrovascular hemodynamics. A study by Zheng et al ( 23 ) found that a 12-week Tai Chi program offers potential benefits for cerebrovascular hemodynamics in elderly individuals at risk of stroke. Moreover, peak oxygen uptake, a prime measure of aerobic capacity and a key predictor of mortality in cardiovascular disease, is approximately 20% higher in Tai Chi practitioners than in inactive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with cardiovascular diseases, including stroke, are recommended to engage in physical activity [ 36 ], which has been associated with the incidence of stroke in adults [ 37 ]. An RCT involving older adults at high risk for ischemic stroke revealed that 12 weeks of tai chi training significantly reduced FBG levels compared to the usual physical activity (control group) ( n = 170) [ 31 ], suggesting that tai chi training provides sufficient improvements in glycemic control of elderly people at high risk for ischemic stroke. Genetic predisposition has been considered one of the major risk factors for diabetes [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Potential Effects Of Mbi On Glycemic Controlmentioning
confidence: 99%